Rancang Sistem Cek Stok Seragam Sekolah Berbasis Supply Chain Management (SCM) Pada UD Rohana - Lubis, Doli Nuddin; Syahputra, Edy Rahman; Lubis, Husni (TIN: Terapan Informatika Nusantara, 2021)
Business competition in the field of selling school uniforms in Medan is currently very tight. UD Rohana is a business unit engaged in the sale and purchase of school uniforms. At UD Rohana itself, at every moment the increasing demand often experiences problems in stocking and distributing existing uniforms to consumers (shops / retailers). This of course will be a loss for UD Rohana in carrying out its business turnaround. For this we need a system that can monitor and check the condition of the stock of goods in several stores. So that if there is an increase in demand or sales in one shop where the demanded goods are accumulated in another shop, then UD Rohana can distribute them to the stores that need them. Supply chain management in the business world has adopted a lot of Supply Chain Management (SCM). With implementing SCM, we can control the existing business processes at UD Rohana. For methods in system development using Rapid Application Development (RAD) and for system business processes using the Unified Modeling Language (UML). The results of this study are the development of a school uniform distribution information system successfully developed by adopting the SCM system.